Foliar Fertilization with Molybdate and Nitrate Up-Regulated Activity of Nitrate Reductase in Lemon Balm Leaves - Kurmet Aitlessov; Bibigul Zhumabekova; Utemurat Sagyndykov; Akmaral Tuyakbayeva; Aliya Bitkeyeva; Karlygash Zh. Bazarbaeva; Abilkhas Mukhtarov; Zhadyrassyn Nurbekova; Mereke Satkanov; Maral Kulatayeva; Karlygash M. Aubakirova; Ardak Nurysheva; et al. (Horticulturae, 2023)
The foliar feeding of soil-grown plants with essential elements such as molybdate can restore their Nitrate reductase activity. However, the activity of nitrate reductase under the foliar feeding of plants with molybdate and nitrate in hydroponic conditions has not been investigated. Thus, we wanted to investigate the effect of the foliar feeding of molybdate and nitrate on the nitrate reductase activity in the leaves of lemon balm plants under hydroponic conditions. Nitrate and molybdate solutions were applied by spraying the leaves of lemon balm plants and the nitrate reductase activity was determined by the colorimetric method. The results of our study demonstrated that the application of molybdate and KNO3 solution enhanced the nitrate reductase activity in the leaves of lemon balm plants. Importantly, our results indicate that foliar fertilization with nitrate and molybdate can improve nitrogen metabolism and carbon fixation in the leaves of lemon balm plants under hydroponic conditions.